PEMBAGIAN WARISAN PADA MASYARAKAT ADAT BATAK TOBA (STUDI DI DESA MARTOBA KECAMATAN SIMANINDO KABUPATEN SAMOSIR) - Sidabutar, Menanti; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Property (vermogen) is all rights and obligations that have people, who have value for money. Thus it can be said that inheritance law is part of the law of wealth. Inheritance law is the provisions that govern the fate of one's wealth after the owner dies. During his life man has wealth. The wealth will not be brought after the owner dies. The wealth will be distributed to those who are entitled to receive it that is the closest offspring of the deceased and or the person appointed to receive it. The deceased is called the heir, while the one who is entitled to receive the treasure is called the heir. In the Tapanuli community ("Batak"), because the heirs are sons (all boys), then surely the inheritance is divided among the heirs (if boys are more than one) while Daughters have no inheritance or are not considered heirs. While this is very contrary to the provisions of Article 852 of the Civil Code.The purpose of writing this thesis namely; First, to know the implementation of inheritance system done by indigenous people batak toba in martoba village, simanindo district, samosir district. Second, to find out the inheritance system of indigenous people batak toba that do not give to the daughter as heir in accordance with justice.This type of research is a sociological law research or as an attempt to see the effect of positive law on the life of the community. From the results of research that has been done then, can be drawn two conclusions; Firstly, the implementation of inheritance in the Batak Toba community in Martoba Village has given inheritance to girls, but still more portion to boys. Second, the inheritance given to girls is now fair even though the share of the division is not the same as the boys and some even are not given to girls. Keywords: Implementation of Inheritance-Inheritance Law -The Traditional Lifestyle of Batak